Comparison of Transient Mitigation through Synchronous Closing and Capacitor Switching in 150 kV Networks - Firdaus; Apriyal, Derry; Azhari Zakri, Azriyenni; Ihsan, Boy; Sultana, Beenish (International Journal of Electrical, Energy and Power System Engineering, 2025)
This study addresses the challenge of transient voltage and current surges caused by capacitor bank switching in high-voltage transmission systems, which can compromise equipment integrity and system stability. The research focuses on optimizing the mitigation of these transients in a 150 kV transmission line using the synchronous closing breaker method. Simulations were conducted in MATLAB/Simulink using actual parameters provided by the power utility. To verify the accuracy of the Simulink model and its results, validation was performed in DIgSILENT PowerFactory by comparing steady-state voltage responses following capacitor switching. With the model validated, three operating scenarios were examined: no capacitor bank, conventional capacitor bank switching, and with the implementation of synchronous closing breakers. The synchronous closing method significantly reduced transient voltage and current magnitudes compared to conventional switching. These outcomes confirm the effectiveness of the synchronous closing breaker in minimizing transient disturbances. The findings contribute to the development of improved transient mitigation strategies and offer a practical reference for large-scale capacitor bank deployment, particularly in smart grid applications. This method provides a cost-effective and scalable approach for improving power quality in modern high-voltage transmission networks.